The Effect of Ginkgo Biloba (EGb 761) on Epileptic Activity in Rabbits - Vesna Vasic; Mirjana Radenkovic; Nada Naumovic; Mira Popovic; Vesna Ivetic (Molecules, 2008)
Different animal models are used to evaluate the process of epileptogenesis. In this investigation the kindling model of epilepsy was used. The epileptic focus was induced in Chinchilla rabbits by stimulation of the hippocampus with electric stimuli. We presumed that the extracts of Ginkgo biloba affect the formation of kindling epilepsy. Bioelectric activity of the brain was registered throughout the development of kindling with and without standardized extracts from dried ginkgo leaves (EGb 761). For each animal the following has been determined: the values of the minimum current strength necessary for the origination of threshold after-discharge (AD) – discharges appearing after the cessation of stimulation; duration of the threshold AD; number of stimulations necessary for the origination of full kindling; time latency for the development of full kindling; number of spontaneous epileptogenic discharges manifested in EEG two days following the formation of full kindling during 60-minute registration. The results show that the process of epileptogenesis was influenced by EGb 761. It has been established that if the animals received EGb 761, significantly weaker minimum current strength was necessary for the development of the epileptogenic focus and the AD were longer, while the number of necessary electrostimulations for the appearance of full kindling was less and the latency was shorter.